Activation of putative transposition intermediate formation in tumor cells - Grigoryan, M S; Kramerov, D A; Tulchinsky, E M; Revasova, E S; Lukanidin, E M (The EMBO journal, 1985)
The transcription levels of two families of mouse repetitive elements namely intracisternal A particle (IAP) genes, and B2 sequences were analyzed in different tumor cells and normal tissues. These sequences belong to two major classes of mobile elements present in the mouse genome. The Northern blots containing poly(A) + RNAs from tumor cells and normal tissues were hybridized to the cloned IAP gene and B2 sequence. The content of IAP gene transcripts in tumor cells is much higher than in normal cells. A 10- to 100-fold difference was found. The predominant IAP-gene specific RNAs in all investigated tumor cells were 9.5, 6.8 and 5.3 kb long. Additional RNA species were found in some of the tumors. The active synthesis of small cytoplasmic B2 RNA transcribed by RNA polymerase III was also detected in most tumor cells tested. Usually it was higher than in normal cells. Free closed circular DNAs hybridizing to IAP gene probes were cloned from Ehrlich ascites carcinoma cells. We speculate that the data obtained indicate the enhanced transposition of mobile elements in tumor cells which may be an important factor of tumor progression.